2016
DOI: 10.1016/j.disc.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Interval edge-colorings of complete graphs

Abstract: An edge-coloring of a graph G with colors 1, 2, . . . , t is an interval t-coloring if all colors are used, and the colors of edges incident to each vertex of G are distinct and form an interval of integers. A graph G is interval colorable if it has an interval t-coloring for some positive integer t. For an interval colorable graph G, W (G) denotes the greatest value of t for which G has an interval t-coloring. It is known that the complete graph is interval colorable if and only if the number of its vertices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Finally, we discuss the improper interval colourings of complete graphs, which is of particular interest due to the ongoing intensive research in [9], [10]. Let z be a vertex of K n such that zx has colour 2.…”
Section: Properties and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we discuss the improper interval colourings of complete graphs, which is of particular interest due to the ongoing intensive research in [9], [10]. Let z be a vertex of K n such that zx has colour 2.…”
Section: Properties and Resultsmentioning
confidence: 99%
“…let t(G) denote the maximum number of colours used in any interval colouring of G. The notion of interval colouring was introduced by Asratian and Kamalian in [1] in connection with specialized scheduling problems and, since then, it was further investigated in many papers, see for example [3], [5], [6], [7], [8], [9], [10]. Not all graphs are proper interval colourable (this concerns, for example, graphs of Class 2); in fact, the problem of determining whether a graph has an interval colouring is NP-complete, even for bipartite graphs, see [2] and [11].…”
Section: Introductionmentioning
confidence: 99%
“…Interval edge-colorings have been intensively studied in different papers. Lower and upper bounds on the number of colors in interval edge-colorings were provided in [3,4] and the bounds were improved for different graphs: planar graphs [5], r-regular graphs with at least 2 ⋅ 𝑟 + 2 vertices [6], cycles, trees, complete bipartite graphs [3], n-dimensional cubes [7,8], complete graphs [9,10], Harary graphs [11], complete k-partite graphs [12], even block graphs [13]. In [14], interval edge-colorings with restrictions on edges were considered.…”
Section: Introductionmentioning
confidence: 99%
“…Interval edge-colorings have been intensively studied in different papers. In [3] it was shown that every tree is from N. Lower and upper bounds on the number of colors in interval edge-colorings were provided in [4] and the bounds were improved for different graphs: planar graphs [5], r-regular graphs with at least 2r + 2 vertices [6], cycles, trees, complete bipartite graphs [3], n-dimensional cubes [7,8], complete graphs [9,10], Harary graphs [11], complete k-parite graphs [12].…”
mentioning
confidence: 99%